ANALYSIS OF STYLISTIC DEVICES IN ENGLISH AND UZBEK PROVERBS CONTAINING MEDICAL LEXEMES (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Proverbs encapsulate deep cultural wisdom and values through concise, often metaphorical language. Those containing medical lexemes offer insights into traditional perceptions of health, illness, and treatment while also showcasing a range of artistic imagery tools. This study explores how metaphors, similes, contrasts, and other figurative devices are employed in proverbs related to medical themes in both English and Uzbek languages. The research finds that artistic imagery in these proverbs enhances their educational, moral, and aesthetic appeal, providing a rich source of linguistic and cultural information.